1996
DOI: 10.1002/(sici)1097-0223(199607)16:7<629::aid-pd922>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Application of a Normal Range for Nuchal Translucency Across the First Trimester

Abstract: Before chorionic villus sampling at 10–13 weeks' gestation, 453 women had the crown–rump length and nuchal translucency (NT) measured with transabdominal ultrasound. There were 19 aneuploid pregnancies (ten cases of trisomy 21, six of trisomy 18, one of 47+marker, one 47,%, and one 45,X mosaic). Average NT was 1·7 mm (range 0–5 mm), correlating with the crown–rump length, but not maternal age. A static cut‐off of 2·5 mm gave a false‐positive rate of 1·3 per cent for crown–rump length between 30 and 35 mm, risi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
3
17
1
2
Order By: Relevance
“…In our study the mean NT thickness in normal fetuses was 1.5 mm, as compared to a study in Taiwanese population, where the mean NT thickness was 1.7 mm (11) . We found that the incidence of NT thickness greater than or equal to 2.5 mm was 2.8% and this observation was in accordance with previous studies (2,8) .The incidence of NT thickness greater than or equal to 2.5 mm in normal fetuses was 2.5% at 11-11.6 weeks at gestation and increased to 5.6% at 13-13.6 weeks, in our study. Other studies have reported that the incidence of NT thickness greater than or equal to 2.5 mm in normal fetuses increased from 1.3% at CRL 30-39 mm to 13.2% at CRL 60-69 mm (8) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study the mean NT thickness in normal fetuses was 1.5 mm, as compared to a study in Taiwanese population, where the mean NT thickness was 1.7 mm (11) . We found that the incidence of NT thickness greater than or equal to 2.5 mm was 2.8% and this observation was in accordance with previous studies (2,8) .The incidence of NT thickness greater than or equal to 2.5 mm in normal fetuses was 2.5% at 11-11.6 weeks at gestation and increased to 5.6% at 13-13.6 weeks, in our study. Other studies have reported that the incidence of NT thickness greater than or equal to 2.5 mm in normal fetuses increased from 1.3% at CRL 30-39 mm to 13.2% at CRL 60-69 mm (8) .…”
Section: Discussionsupporting
confidence: 93%
“…(4,7,8) .Therefore, in screening chromosomal defects, the use for a fixed cut-off in NT thickness is inappropriate and each measurement should be examined according to the CRL. (9) Multiple of median values to express the relationship between NT measurements and gestational age can be used (10).…”
Section: Discussionmentioning
confidence: 99%
“…The median nuchal-translucency thickness ranged from 1.0 mm to 4.0 mm at the different centers (the expected median value is approximately 1.5 mm and is known to increase with gestational age). 23 The overall rate of detection of Down's syndrome (based on a criterion of nuchaltranslucency measurements above the 95th percentile for each center) was 31 percent, with a 5 percent false positive rate. The variability among centers in median values and in the ratios of the 95th percentile to the 50th percentile, coupled with their vary-ing ability to obtain the measurements successfully, suggests that the performance of this indicator in our study might not accurately reflect its long-term performance at individual centers.…”
Section: Resultsmentioning
confidence: 99%
“…Elle est corrélée à l'âge gestationnel chez un foetus normal [13,14]. Après 14 SA, il existe une disparition spontanée de cette hyperclarté nucale [15], phénomène surtout visible chez le foetus à caryotype normal, alors qu'en cas d'aneuploïdies, elle tend à augmenter [16].…”
Section: Discussionunclassified